2016
DOI: 10.1016/j.carbon.2014.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced human bone marrow mesenchymal stem cell chondrogenic differentiation in electrospun constructs with carbon nanomaterials

Abstract: Cartilage as a tissue in the body possesses a low regenerative capacity and is extremely difficult to repair. Today, treatment of cartilage injury, degeneration and defects presents critical clinical challenges, yet none of the currently available cartilage treatments provides a perfect solution. Since natural cartilage extracellular matrix is a nanoscaled structure, the main objective of this study is to design a novel biomimetic nanostructured cartilage construct via electrospinning and carbon nanomaterials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 75 publications
1
38
0
Order By: Relevance
“…Scaffolds with SWCNT-based nanomaterial have greatly enhanced GAG synthesis and chondrogenic differentiation of hMSCs within 2 weeks. 17 Applications of different biomaterials in chondrocyte tissue engineering show that soft fiber condition generally promotes greater degree of chondrogenesis and RGD (arginylglycylaspartic acid) density, an element for cellular recognition which is a critical regulator of this lineage commitment. 73 CNT-coated coverslip is a rigid structure with lack of softness, which might have caused the decrease in gene expression during the latter half of the study.…”
Section: Chondrogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaffolds with SWCNT-based nanomaterial have greatly enhanced GAG synthesis and chondrogenic differentiation of hMSCs within 2 weeks. 17 Applications of different biomaterials in chondrocyte tissue engineering show that soft fiber condition generally promotes greater degree of chondrogenesis and RGD (arginylglycylaspartic acid) density, an element for cellular recognition which is a critical regulator of this lineage commitment. 73 CNT-coated coverslip is a rigid structure with lack of softness, which might have caused the decrease in gene expression during the latter half of the study.…”
Section: Chondrogenic Differentiationmentioning
confidence: 99%
“…[7][8][9][10] Recently, it has been shown that CNT-based scaffolds promote the proliferation and lineagespecific differentiation of human and rat MSCs. [11][12][13][14][15][16][17][18][19] Successful differentiation studies of human embryonic stem cells have also been carried out using CNTs as scaffold materials. [20][21][22] CNTs are also currently being used in other biomedical applications, such as cell tracking and labeling, nanosensors, and controlled delivery of drugs and bioactive agents.…”
Section: Introductionmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T 20 nHAp/CNT [67], polymeric nanofibers/nHAp [68] and polymeric nanofibers/carbon nanomaterials [69,70]. However, in all of these published papers, the researchers only explored either nHAp alone or its combination with carbon nanomaterials isolated and/or inside polymeric ultrathin fibers, not outside and aligned as demonstrated here using a 3D scaffold.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…One of the most promising nanometer-sized cylinders that could imitate nanofibers present in native ECM, are carbon nanotubes (Ng et al 2012). Holmes et al (2014) in their research project showed that the mechanical properties of polycaprolactone synthesized scaffold resulting from electrospinning method are improved in the presence of Carboxylated-SWCNT and chondrogenic adhesion, proliferation and differentiation of the stem cells of bone marrow in such scaffold are increased in comparison with polycaprolactone control scaffolds lacking Carboxylated-SWCNT. Ge et al (2012) too, have carried out comprehensive research into functional biomaterials in connection with cartilage tissue.…”
Section: Introductionmentioning
confidence: 99%